VIRTUAL COMMUNITIES, GENDER AND IDENTITY IN YOUNG UNIVERSITY STUDENTS OF LIMA - BENITES MEDINA, Marcela (2023)
The article analyzes in the young university students of Lima the constitution of virtual communities, gender relations and the construction of their identity. The participation of young people in virtual spaces contributes to the understanding of new forms of socialization, interaction and youth subjectivities. It was found that the majority of young people belong to virtual communities of friends, they relate indistinctly with men and women, the themes that link them are oriented by affective values and by themes of utilitarian practices. Likewise, their identity is characterized by being plural, founded on feelings and values that highlight their own individuality, develop an image that seeks the recognition of others and the sense of belonging to virtual communities.